Perbandingan Hukum Tindak Pidana Aborsi di Indonesia dengan Kebijakan Praktik Aborsi di Kanada - A.H Sofiyullah (International Forum of Researchers and Lecturers, 2024)
This study aims to compare the legal framework governing the criminal offense of abortion in Indonesia with the policy on abortion practices in Canada. Using the comparative law method, this analysis investigates aspects of the law relating to abortion, including laws, regulations, and court decisions in both countries. Cultural, religious and social factors are also considered in the context of the different legal approaches to abortion in the two countries. The results highlight significant differences in legal approaches and societal views towards abortion between Indonesia and Canada. The implications of this comparison are discussed to enrich the understanding of abortion law and generate ideas for policy reforms or adjustments appropriate to each country's context. This research contributes to a global understanding of the legal and moral issues related to abortion and provides a foundation for further discussion in developing more effective and humane policies related to abortion at the national and international levels.